Neurocognitive Markers During Prolonged Breath-Holding in Freedivers: An Event-Related EEG Study - Steinberg, Fabian; Doppelmayr, Michael (Frontiers in Physiology, 2019)
Since little is known concerning the psychological, cognitive and neurophysiological factors that are involved in and important for phases of prolonged breath-holding (pBH) in freedivers, the present study uses electroencephalography (EEG) to investigate event-related neurocognitive markers during pBH of experienced freedivers that regularly train pBH. The purpose was to determine whether the well-known neurophysiological modulations elicited by hypoxic and hypercapnic conditions can also be detected during pBH induced hypoxic hypercapnia. Ten experienced free-divers (all male, aged 35.10 ± 7.89 years) were asked to hold their breath twice for four minutes per instance. During the first pBH, a checker board reversal task was presented and in the second four-min pBH phase a classical visual oddball paradigm was performed. A visual evoked potential (VEP) as an index of early visual processing (i.e., latencies and amplitudes of N75, P100 and N135) and the latency and amplitude of a P300 component (visual oddball paradigm) as an index of cognitive processing were investigated. In a counter-balanced cross-over design, all tasks were once performed during normal breathing (B) and once during pBH. All components were then compared between an early pBH (0–2 min) and a later pBH stage (2–4 min) and with the same time phases without pBH (i.e., during normal breathing). Statistical analyses using analyses of variance (ANOVA) revealed that comparisons between B and pBH yielded no significant changes either in the amplitude and latency of the VEP or in the P300. This indicates that neurocognitive markers, whether in an early visual processing stream or at a later cognitive processing stage, were not affected by pBH in experienced free-divers.